2012
DOI: 10.1186/1471-2369-13-174
|View full text |Cite
|
Sign up to set email alerts
|

Culture-negative subacute bacterial endocarditis masquerades as granulomatosis with polyangiitis (Wegener’s granulomatosis) involving both the kidney and lung

Abstract: BackgroundSubacute bacterial endocarditis (SBE) occasionally exhibits positive cytoplasmic anti-neutrophil cytoplasmic antibody (c-ANCA) of the anti-proteinase-3 (PR-3) type. Clinically, it mimics ANCA-associated vasculitis, such as Wegener's disease with glomerulonephritis. Lung abscesses are the most common manifestation of lung involvement. We herein report a case of culture-negative SBE strongly c-ANCA/PR3-positive accompanied by pulmonary involvement and glomerulonephritis. In this case, we took biopsies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 9 publications
0
28
0
1
Order By: Relevance
“…Similar to our study, aortic regurgitation was common in the Lacoste et al study, but none of the patients had tricuspid valve lesion. However, our systematic review comprised three cases including our report with tricuspid valve vegetations and sterile serum; two patients have eventually improved while our patient died.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, aortic regurgitation was common in the Lacoste et al study, but none of the patients had tricuspid valve lesion. However, our systematic review comprised three cases including our report with tricuspid valve vegetations and sterile serum; two patients have eventually improved while our patient died.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent cohort studies have shown that neurologic involvement [8] or micro bleedings diagnosed by cerebral MRI can be seen not only in AAV patients but also in patients with infectious endocarditis-associated GN (emboli) [7]. In addition, pulmonary inflammatory granulomas, which are more frequently seen in idiopathic AAV patients, have also been reported in ANCA-positive infectious endocarditisassociated GN [10]. On the other hand, fever (a typical sign of infection) can be absent in some patients with ANCA positive infectious endocarditis-associated GN [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Literature regarding the appropriate treatment of patients with ANCA positive infectious endocarditis-associated GN is currently not consistent. Some propose treatment with antibiotics alone [10], others propose a combination of antibiotics and steroids [11,[18][19][20] and a third group suggest surgery followed by antibiotics without steroids [21]. Interestingly, in 1998 Haseyama et al [19] proposed that patients with ANCA positive infectious endocarditis-associated GN and low titers of PR3 ANCA (e.g., below 25 IU/ml) can be treated with antibiotics alone, while patients with higher titers of PR3 ANCA antibodies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, hasta un 16 % de las endocarditis pueden cursar sin fiebre 2 ni leucocitosis, siendo incluso en algunos casos los hemocultivos negativos 3,4 .…”
Section: Discussionunclassified